An Empirical Analysis of Illegal Insider Trading. - Meulbroek, Lisa K (Journal of Finance, 1992)
Whether insider trading affects stock prices is central to both the current debate over whether insider trading is harmful or pervasive, and to the broader public policy issue of how best to regulate securities markets. Using previously unexplored data on illegal insider trading from the Securities and Exchange Commission, this paper finds that the stock market detects the possibility of informed trading and impounds this information into the stock price. Specifically, the abnormal return on an insider trading day averages 3 percent, and almost half of the pre-announcement stock price run-up observed before takeovers occurs on insider trading days. Both the amount traded by the insider and additional trade-specific characteristics lead to the market's recognition of the informed trading.